2005
DOI: 10.1152/japplphysiol.00816.2004
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanics of muscle tendinous junction of canine diaphragm

Abstract: The diaphragmatic muscle tendon is a biaxially loaded junction in vivo. Stress-strain relations along and transverse to the fiber directions are important in understanding its mechanical properties. We hypothesized that 1) the central tendon possesses greater passive stiffness than adjacent muscle, 2) the diaphragm muscle is anisotropic, whereas the central tendon near the junction is essentially isotropic, and 3) a gradient in passive stiffness exists as one approaches the muscletendinous junction (MTJ). To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…The high transverse stiffness of the muscle at the myotendinous junction and inextensibility of the central tendon combine to eliminate stress concentrations at the muscle-tendon interface, and may play an important role in preventing injury. [43] Consistent with the natural distribution and function of utrophin at the myotendinous junction we found that microutrophin was highly-enriched at this anatomical location (Fig. 3).…”
Section: Discussionsupporting
confidence: 83%
“…The high transverse stiffness of the muscle at the myotendinous junction and inextensibility of the central tendon combine to eliminate stress concentrations at the muscle-tendon interface, and may play an important role in preventing injury. [43] Consistent with the natural distribution and function of utrophin at the myotendinous junction we found that microutrophin was highly-enriched at this anatomical location (Fig. 3).…”
Section: Discussionsupporting
confidence: 83%
“…The tendinous intersections are thought to function, at least in part, to provide transverse strength to the RA by giving it anchor points along its length (McGill 2002). For this to function as hypothesized, the transverse stiffness of the tendinous region must be greater than the muscle region, which has been shown to be true for the diaphragm muscle (Hwang et al 2005b). The lateral movement of the RA muscle should be dictated by the competing forces generated by the RA muscle, which will stiffen its fibres both along and transverse to its fibre direction, and the forces generated in the abdominal wall muscles (EO, IO, TrA), which will act to pull the RA muscle transversely across its fibres.…”
Section: Discussionmentioning
confidence: 85%
“…In general, these tissues can be thought as a matrix of protein fibres, primarily collagen, at varying degrees of parallel or random arrangement, encompassed within a gel-like ground substance. The assortment of compositions of these structures in different connective tissues allows for many unique properties that have been recorded in tissues such as skin (Lees et al 1991), artery (L'Italien et al 1994) and diaphragm central tendon (Hwang et al 2005b), suitable to the demands placed on these tissues. With the range of demands placed on the abdominal wall muscles and tissues, it is reasonable to expect quite distinctive deformations during contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Others described the mechanical attributes of the musculotendinous junction in the diaphragm of canines, supporting the notion that stiffness continuity exists between these parts [8].…”
Section: Introductionmentioning
confidence: 85%